2016
DOI: 10.1007/s11096-016-0381-7
|View full text |Cite
|
Sign up to set email alerts
|

The status of the performance of medication reviews in German community pharmacies and assessment of the practical performance

Abstract: Background Pharmacist-led medication reviews have shown to prevent drug-related problems (DRPs). So far, data is rare about the implementation in routine care, the conditions for intensifying this service and the practical skills of community pharmacists to perform medication reviews. Objective To assess the current status of medication review implementation in German community pharmacies and the performance of identifying DRPs in a ficticious patient example. Setting German community pharmacies. Method An onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Although pharmacy-based medication reviews provide a systematic means to identify and resolve DRPs, they are still rare in routine care in Germany [15]. During the dispensing process, DRP detection is restricted to drugs dispensed at that time [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Although pharmacy-based medication reviews provide a systematic means to identify and resolve DRPs, they are still rare in routine care in Germany [15]. During the dispensing process, DRP detection is restricted to drugs dispensed at that time [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The potential influence of the training may also explain the good results concerning the identification of PIM since it was one of the main topics during the pharmacists’ training in this study. Greissing et al found a lower agreement rate between DRPs identified by untrained German community pharmacists and predefined DRPs in a fictitious patient example [29]. In that study, 97% of 143 participating pharmacists did not identify PIM.…”
Section: Discussionmentioning
confidence: 86%
“…In the survey period, 1975 persons subscribed to the professional newsletter. On the basis of response rates in other online surveys among community pharmacists in Germany [24,25], we aimed to reach a sample size of at least 8-10% of all subscribers.…”
Section: Participants and Settingmentioning
confidence: 99%